A new species of the Hypsiboas pulchellus group from the Serra da Mantiqueira, southeastern Brazil (Amphibia: Anura: Hylidae) - Pinheiro, Paulo D. P. (2016)
A new species of the Hypsiboas pulchellus group is described from the Mantiqueira range, in the Município de Rio Preto, State of Minas Gerais, Brazil. We describe adults, tadpoles, and the advertisement call. The new species is morphologically similar to H. freicanecae, a species known from a few localities in the states of Alagoas and Pernambuco, northeastern Brazil, ∼1640 km north. Adults differ from H. freicanecae in having a slender body, smaller male size, larger calcar, and hidden surfaces of thighs and feet orange in life. Tadpoles have a ventral oral disc, with labial tooth row formula 2(2)/3–4(1), with one to three narrow posterior gaps on the marginal papillae located on the oral disc emarginations. The advertisement call is composed of two nonpulsed notes with dominant frequency at the second harmonic. The species is known only from its type locality, in an unprotected area.